FIGURATIVE LANGUAGES IN EIGHT SELECTED SONGS IN “WHAT IS LOVE?” ALBUM BY CLEAN BANDIT - Yulistina, Amelia; Mustikawati, Yunitari; Nur, Riola Haya (ELITERATE : Journal of English Linguistics and Literature Studies, 2024)
"What is love?" is the second studio album by British electronic band Clean Bandit to talk about what love is. This album consists of 16 songs, and we have chosen 8 songs to be analyzed. The reason why we chose these eight songs is because they are popular and contain figurative language in them. This study aims to analyze the figurative language of the selected song lyrics. The research method used is a descriptive qualitative method. We analyzed the types of figurative language and the meaning of the song lyrics. This study found several findings. There are 28 figurative languages contained in the 8 selected songs which are divided into seven metaphors, six similes, one personification, two metonymy, two allegories, one paradox, eight hyperboles, one litotes. We found that the most common figurative language found in songs entitled "Out of Night" has four, "Solo" has six, "Tears" has five, "Symphony", "mama" has two each, “Nowhere” and “Should've Known Better” have three each, and “Beautiful” has one. In conclusion, this album has a lot of figurative language and uses 12 types of figurative language. There are many figurative meanings in the album.